LITERATUR REVIEW OF RADIOGRAPHIC MANAGEMENT EXAMINATION OF THE URINARY SYSTEM - shelly; Riana Riau Azzahra, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
The urinary system is an organ system that produces, stores and drains urine. Disorders of the urinary system are one of the disorders that are often found in Indonesia. Radiology is usually used as a support to detect abnormalities in the urinary system. One of the examinations carried out is a radiographic examination using contrast media. There are several types of examination techniques that are often used to diagnose diseases related to the urinary system, namely blast nier overzicht intravenous pyelography (BNO-IVP), bipolar voiding urethrocystography (BVUC), retrograde urethrography, and cystography. The aim of this research is to determine the management of radiographic examinations of the urinary system, as well as to determine the reasons for the differences found between theory and previous research. This type of research is a literature review using descriptive qualitative research methods. This research used 13 research journals which were analyzed according to the research objectives. This research was conducted from March to May 2024. The results of this research show that 13 journals provide complete information regarding the management of radiographic examinations of the urinary system, including patient preparation, preparation of tools and materials, and the examination techniques carried out. Finding differences between theory and research that has been carried out, it can be concluded that the differences in patient preparation, preparation of tools and materials, as well as examination techniques have the aim of assisting doctors in maximally establishing a diagnosis. Keywords: Urinary system, Radiographic Examination, Contrast Media The urinary system is an organ system that produces, stores and drains urine. Disorders of the urinary system are one of the disorders that are often found in Indonesia. Radiology is usually used as a support to detect abnormalities in the urinary system. One of the examinations carried out is a radiographic examination using contrast media. There are several types of examination techniques that are often used to diagnose diseases related to the urinary system, namely blast nier overzicht intravenous pyelography (BNO-IVP), bipolar voiding urethrocystography (BVUC), retrograde urethrography, and cystography. The aim of this research is to determine the management of radiographic examinations of the urinary system, as well as to determine the reasons for the differences found between theory and previous research. This type of research is a literature review using descriptive qualitative research methods. This research used 13 research journals which were analyzed according to the research objectives. This research was conducted from March to May 2024. The results of this research show that 13 journals provide complete information regarding the management of radiographic examinations of the urinary system, including patient preparation, preparation of tools and materials, and the examination techniques carried out. Finding differences between theory and research that has been carried out, it can be concluded that the differences in patient preparation, preparation of tools and materials, as well as examination techniques have the aim of assisting doctors in maximally establishing a diagnosis. Keywords: Urinary system, Radiographic Examination, Contrast Media